A dynamic version of Okun's law in the EU15 countries - The role of delays in the unemployment-output nexus - Thomas Obst (European University Viadrina, Department of Business Administration and Economics, 2019)
This paper estimates Okun's law in the EU15 countries between 1980 and 2018. It employs three different versions of the law with a focus on the dynamic part of the relationship. We find that the negative relationship between unemployment and output holds for most countries and is fairly stable over time. However, Okun's coefficient varies substantially across countries. The dynamic version can shed light on the different country estimates found in the literature and is useful to assess the stability of the law. The paper argues that lag effects need to be taken into account to avoid possible misspecification of the short run unemployment-output relationship. A mixed lag structure indirectly controls for missing explanatory variables and includes possible asymmetries.
Keywords: E24; C22; E32; 330; Okun's law; unemployment; growth; dynamic modelling; cycles